Analisis Kualitas Layanan Sistem Informasi Transportasi LRT Kota Palembang Menggunakan ITIL 4 Studi Literatur - Ahmad Subarkah; M. Dicky; Salman Alfahiri; Eriene Dheanda Absharina (STEKOM PRESS, 2026)
The development of information technology drives the improvement of service quality in various sectors, including public transportation. Technology-based transportation services such as the Palembang LRT utilize information systems in their operations, such as electronic ticketing systems and the delivery of travel information to users, making the quality of information technology services an important factor in determining user satisfaction as well as the overall success of the service. analyzing the service quality of the information system at Palembang LRT using the ITIL 4 framework. The method used is a literature review by examining various previous studies that are relevant within the last five years. shows that the implementation of ITIL 4 is able to improve the quality of information technology services, especially through the practices of incident management, problem management, and service request management. The analysis also shows that the aspects of reliability, responsiveness, availability, and user satisfaction are the main indicators in assessing IT service quality. Nevertheless, there are still potential issues such as disruptions in the ticket system and delays in information delivery that can affect the user experience. Therefore, it is recommended to implement ITIL 4 gradually, enhance system monitoring, and optimize the service desk to improve IT service quality. Thus, it is expected that LRT Palembang services can provide a better experience for users and increase public trust in technology-based public transportation.